2021
DOI: 10.3390/ijerph182312276
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Inequalities in the Incidence of Acute Myocardial Infarction among Beijing Townships, 2007–2018

Abstract: Acute myocardial infarction (AMI) poses a serious disease burden in China, but studies on small-area characteristics of AMI incidence are lacking. We therefore examined temporal trends and geographic variations in AMI incidence at the township level in Beijing. In this cross-sectional analysis, 259,830 AMI events during 2007–2018 from the Beijing Cardiovascular Disease Surveillance System were included. We estimated AMI incidence for 307 consistent townships during consecutive 3-year periods with a Bayesian sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As one of the most populous cities in China, Beijing shoulders a huge burden of AMI, with an incident rate of 231.6 per 100,000 in 2016–2018 ( 26 ). Moreover, an upward tendency of extreme precipitation was observed in Beijing and China under the scenario of global warming ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most populous cities in China, Beijing shoulders a huge burden of AMI, with an incident rate of 231.6 per 100,000 in 2016–2018 ( 26 ). Moreover, an upward tendency of extreme precipitation was observed in Beijing and China under the scenario of global warming ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, AMI is still the main cause of death in patients with CAD worldwide. AMI is responsible for significant patient morbidity and mortality, especially in China, where these rates have been increasing annually [ 3 , 4 ]. Epidemiological studies related to AMI have shown that male sex, hyperlipidaemia, smoking, stress, diabetes, hypertension, age, obesity, family history and a sedentary lifestyle all culminate in the development of AMI [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although more than 70% of patients in urban areas lived within a 15-min drive to a PCI hospital in 2019, approximately 70% of peri-urban patients had a drive time of more than 15 min. Additionally, our previous work showed that rapid increases in AMI incidence were particularly evident in Beijing’s peri-urban areas [ 29 ]. These findings allow for the identification of within-city health care disparities to inform policy-making and cost-effective allocation of health resources.…”
Section: Discussionmentioning
confidence: 99%